Arms and Armour of Krakow in the First Half of the 17th century - Zinkiewicz, Jacek (Tools of War, 2023)
It seems that the first half of the 17th century was a period of relative peace in the history of Krakow. From the siege of the city by Habsburg troops in 1587 until the tragic events of 1655, Krakow was not besieged by enemy troops. It was also a time when the threat was not forgotten and efforts were made to counteract it in advance. The preserved sources allow for the presentation of many aspects of urban defense in the discussed period. The example of the former capital of the Polish-Lithuanian Commonwealth shows the urban defense of that time in quite a wide range. Thanks to the preserved registers, but also other written sources, especially normative ones, we can attempt to characterize the city's armament in the time preceding the series of tragic events that began in the mid-17th century. The characteristics of urban weapons in modern times is a very poorly explored issue. This also contrasts with the abundance of historical studies on modern military affairs. This article is an attempt to partially fill this research gap.